Nutritional Value of Lime and Lemon in Hypercholesterolaemic Induced Rats - Ajugwo, Anslem O; Erhabor, Tosan; Mokogwu, Tom; Digban, Kester; Ojieh, Godwin; Nnatuanya, Issac (Asian Journal of Medical Sciences, 2013)
OBJECTIVE: People generally use lime and lemon when weight reduction is anticipated. This work was carried out to determine the effect of these fruits in hypercholesterolaemic induced rats. MATERIALS AND METHOD: Sixteen (16) albino rats were used and grouped into four groups of four (4) each. The rats were allowed to acclimatize and fed with egg yolk for seven days to induce hypercholesterolaemic state. Water, lemon, lime and lime+lemon were administered to these groups respectively. Cholesterol level was analyzed in all the groups after two (2) weeks of the administration of the fruits. RESULTS: The result showed a statistical decrease in the groups treated with lime, lemon and lime+lemon. The lime+lemon group showed a more significant decrease (p<0.05) in both cholesterol level and body weight when compared with the control group and other groups. This reduction may be as a result of the contents of the fruits. CONCLUSION: It can therefore be concluded that lime and lemon helps in the lowering of blood cholesterol level and body weight. DOI: http://dx.doi.org/10.3126/ajms.v3i1.5450 Asian Journal of Medical Sciences 3(2012) 13-16